Transcriptomic profiling of the human brain reveals that altered synaptic gene expression is associated with chronological aging. Issue 1 (December 2017) - Dillman, Allissa; Majounie, Elisa; Ding, Jinhui; Gibbs, J.; Hernandez, Dena; Arepalli, Sampath; Traynor, Bryan; Singleton, Andrew; Galter, Dagmar; Cookson, Mark
Abstract Aging is a biologically universal event, and yet the key events that drive aging are still poorly understood. One approach to generate new hypotheses about aging is to use unbiased methods to look at change across lifespan. Here, we have examined gene expression in the human dorsolateral frontal cortex using RNA- Seq to populate a whole gene co-expression network analysis. We show that modules of co-expressed genes enriched for those encoding synaptic proteins are liable to change with age. We extensively validate these age-dependent changes in gene expression across several datasets including the publically available GTEx resource which demonstrated that gene expression associations with aging vary between brain regions. We also estimated the extent to which changes in cellular composition account for age associations and find that there are independent signals for cellularity and aging. Overall, these results demonstrate that there are robust age-related alterations in gene expression in the human brain and that genes encoding for neuronal synaptic function may be particularly sensitive to the aging process.